2004
DOI: 10.2134/jeq2004.2243
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vegetated Buffer Strips for Retaining Cryptosporidium parvum

Abstract: Overland and shallow subsurface hydrologic transport of pathogenic Cryptosporidium parvum oocysts from cattle feces into surface drinking water supplies is a major concern on annual grasslands in California's central and southern Sierra Nevada foothills. Soil boxes (0.5 m wide x 1.1 m long x 0.3 m deep) were used to evaluate the ability of grass vegetated buffer strips to retain 2 x 10(8) spiked C. parvum oocysts in 200-g fecal deposits during simulated rainfall intensities of 30 to 47.5 mm/h over 2 h. Buffers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…We calculated the percentage of total number (cfu) of E. coli retained within the wetland during each event from the difference between inflow and outflow load, and found that percent reduction ranged from 33% to 91%, with an average of 73% (table 1). These results are comparable to previous findings that relatively narrow (1 to 2 yards wide) vegetative buffer strips can reduce E. coli and C. parvum in runoff by as much as 90% to 99% on California's annual grasslands under rainfall-runoff conditions (Atwill et al 2002(Atwill et al , 2006Tate et al 2004Tate et al , 2006. Reductions of 80% to 99% have been seen for E. coli and fecal coliforms with the use of constructed surfaceflow wetlands to treat municipal and Top left, channelized runoff from the pasture was collected in a small basin.…”
Section: Effects On E Coli Concentrationssupporting
confidence: 85%
See 1 more Smart Citation
“…We calculated the percentage of total number (cfu) of E. coli retained within the wetland during each event from the difference between inflow and outflow load, and found that percent reduction ranged from 33% to 91%, with an average of 73% (table 1). These results are comparable to previous findings that relatively narrow (1 to 2 yards wide) vegetative buffer strips can reduce E. coli and C. parvum in runoff by as much as 90% to 99% on California's annual grasslands under rainfall-runoff conditions (Atwill et al 2002(Atwill et al , 2006Tate et al 2004Tate et al , 2006. Reductions of 80% to 99% have been seen for E. coli and fecal coliforms with the use of constructed surfaceflow wetlands to treat municipal and Top left, channelized runoff from the pasture was collected in a small basin.…”
Section: Effects On E Coli Concentrationssupporting
confidence: 85%
“…This relationship can be attributed to the fact that higher runoff rates increase the tailwater's capacity for pollutant mobilization and transport. In other studies, we have found that runoff rate is positively correlated with the load of E. coli and C. parvum discharged from cattle fecal deposits on annual grasslands under rainfall-runoff conditions (Atwill et al 2002;Tate et al 2004Tate et al , 2006.…”
Section: Effects On E Coli Concentrationsmentioning
confidence: 61%
“…A set of BMPs that were either already in practice by one or more dairy farms or newly installed for this project were evaluated. These included modifying the density of cattle or completely excluding cattle from the lot during the duration of the rainfall season, using a tractor to scrape and remove the accumulated layer of manure from the lot prior to the onset of winter rains, and channeling runoff from the lot through vegetative buffer strips as a means to reduce the load of waterborne microbial contaminants (2,3,8,27,29). Building upon these preexisting practices, we implemented vegetative surface treatments in October, prior to the onset of winter rains, for a subset of the dairy lots.…”
Section: Methodsmentioning
confidence: 99%
“…These large fluxes of fecal coliforms suggest that enteric pathogens shed by infected cattle may also be present in runoff from similar high-cattle-use areas, given the abilities of bacterial and protozoal microorganisms shed in bovine feces to be eluted from fresh fecal matrices and entrained in overland flow during precipitation (2,3,5,8,27,28). Given the common occurrence of Giardia duodenalis in dairy cattle herds (21,22,30,31), the apparent low infectious dose of this protozoal parasite for healthy human volunteers (24), the fact that Tomales Bay is a major shellfish growing region in central California, and the abilities of oysters and other bivalves to concentrate Giardia cysts from the water column (10), we revisited a subset of these original dairies monitored by Lewis et al (16) to (i) identify climatic and on-farm risk factors associated with high concentrations of cysts or high instantaneous loads (cysts/second) of G. duodenalis in storm-based runoff from these high-cattle-use areas and (ii) evaluate the efficacies of selected BMPs to reduce the concentration or instantaneous load of G. duodenalis in storm runoff compared to that in adjacent control sites.…”
mentioning
confidence: 99%
“…From a management standpoint the issues of sediment, nutrient and pathogen contaminants have collectively been addressed using stream-side vegetation buffer strips in an attempt to attenuate pollutant entry into stream systems (Castelle et al, 1994;Schmitt et al, 1999;Dosskey 2002;Dorioz et al, 2006;Mayer et al, 2007). Vegetation buffers have been effective at reducing nutrient (Yates and Sheridan, 1983;Lowrance et al, 1985), pathogen (Tate et al, 2004;Knox et al, 2007) and sediment loading (Lyons et al, 2000;Lee et al, 2003) in streams. However, development of effective policy concerning the use of buffer strips has been complicated by the fact that the efficacy of buffers in reducing pollutant loading varies strongly in accordance with a number of design and environmental factors including buffer width, cover and height of plant material, slope, and soil attributes (Pearce et al, 1997, Atwill et al, 2005, George et al, 2011.…”
Section: Modern Agriculture and Water Quality Of Free-flowing Streamsmentioning
confidence: 99%